2016
DOI: 10.1007/s12035-016-9759-8
|View full text |Cite
|
Sign up to set email alerts
|

MiRNAs are involved in chronic electroacupuncture tolerance in the rat hypothalamus

Abstract: Acupuncture tolerance is the gradual decrease in analgesic effect due to its prolonged application. However, its mechanism in terms of miRNA is still unknown. To explore the role of miRNAs in electroacupuncture (EA) tolerance of rats using deep sequencing, rats with more than a 50 % increase in tail flick latency (TFL) in response to EA were selected for this experiment. EA tolerance was induced by EA once daily for eight consecutive days. The hypothalami were harvested for deep sequencing. As a result, 49 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…These findings are supported by additional studies showing a possible correlation between Ago2/miRNAs complex regulation and DA neurons plasticity during opiate addiction . It was also reported that the expression levels of miRNAs could be regulated by EA . Therefore, we speculated that circRNAs might play a role in the regulation of morphine reinforcement processes.…”
Section: Introductionsupporting
confidence: 80%
“…These findings are supported by additional studies showing a possible correlation between Ago2/miRNAs complex regulation and DA neurons plasticity during opiate addiction . It was also reported that the expression levels of miRNAs could be regulated by EA . Therefore, we speculated that circRNAs might play a role in the regulation of morphine reinforcement processes.…”
Section: Introductionsupporting
confidence: 80%
“…Studies showed that the expression of multiple miRNAs has changed such as miR-129 ( Zhu et al, 2018 ) and miR-195 ( Shi et al, 2013 ) after PNI. It has been reported that EA enhanced neurobehavioral functional recovery against ischemic stroke through targeting of SOX2-mediated axonal regeneration by miR-132 ( Cui et al, 2017 ; Zhao X. et al, 2018 ). Another research suggested that several miRNAs were involved in chronic electroacupuncture tolerance in the rat hypothalamus ( Cui et al, 2017 ; Zhao X. et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that EA enhanced neurobehavioral functional recovery against ischemic stroke through targeting of SOX2-mediated axonal regeneration by miR-132 ( Cui et al, 2017 ; Zhao X. et al, 2018 ). Another research suggested that several miRNAs were involved in chronic electroacupuncture tolerance in the rat hypothalamus ( Cui et al, 2017 ; Zhao X. et al, 2018 ). Our previous studies have confirmed that EA could promote SC migration and NGF expression in injured local nerve as well as BDNF ( Hu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research showed that hypothalamus let-7, miR-148a, miR-124, miR-107 and miR-370 were confirmed to be related to EA tolerance (Cui et al, 2017 ). EA pretreatment had a protective effect on ischemia/reperfusion injury via miR-214 (Liu et al, 2014 ) and miR-124 (Chen S. H. et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%